TP3-3 Why do some patients fail to respond to VNS? – a retrospective analysis of cardiac based seizure detection (CBSD) therapy. Issue 3 (14th February 2019) - Wysota, B; Samarasekera, S; Hamilton, P; Soryal, I
Abstract : Objectives: To identify predictors of poor response to cardiac based seizure detection (CBSD) VNS therapy. Design: Data was collected retrospectively for patients with epilepsy who had VNS Aspire SR implanted between June 2014 and June 2017. 51 patients who reached a therapeutic level of stimulation were included. We compared those who achieved significant seizure reduction (at least 50%) with the remainder to identify potential factors predicting response. Subjects: 51 patients achieving therapeutic stimulation (1.5mA) with the VNS Aspire SR. Methods: We reviewed patients' electronic records over the period between June 2014 and June 2018. Results: 32 (63%) patients achieved significant seizure reduction. The following factors applied equally to both responders and non-responders: patient age, duration of epilepsy prior to VNS insertion, seizure type, the presence of a causative structural abnormality and the presence of a carer. Co-existing learning disability and/or non-epileptic attacks were commoner among poor responders. Polytherapy (3 or more AEDs) and non-compliance with medical treatment were also commoner among the poor responders; none of these factors was statistically significant. Conclusions: Factors potentially predicting response to resective surgery (including patients' age and duration of epilepsy) do not necessarily predict response to VNS therapy. The presence of a learning disability and the extent of seizure refractoriness may influence response to VNS therapy; a larger study is needed to assess their significance.